(untitled) (AmeriQuests, 2015)
Much has been published and discussed in relation to Edgar Allan Poe’s and Charles Baudelaire’s intertextual dialogues, as well as to the French reception of Poe’s writings and aesthetic theories through Baudelaire’s translations and essays. Likewise, there have been several studies in Brazil comparing Poe’s and Brazilian writer Machado de Assis’ short stories and individual aesthetic theories, as well as studies regarding Baudelaire’s aesthetic reception in 19th century Brazilian literature. However, despite some academic studies and papers in Brazil referring more closely to their literary projects and their possible intertextual bindings, a deeper study into how Machado de Assis may have actually read and subverted Poe’s writings so as to fit it within his own framework and thus help foster his project of defending the formation of a national literary identity still needs to be carried out. The same may be said about both Baudelaire’s role in Poe and Machado de Assis’ literary encounter and Machado de Assis’ reception of Baudelaire’s aesthetic theories and poetics. In this paper, therefore, I want to take a transatlantic voyage while addressing the question of how Machado de Assis may have actually incorporated and, paradoxically, subverted Poe’s and Baudelaire’s imagery, topoi and aesthetics into his own literary project. Two broad aspects regarding the three authors’ writings will be tackled: the universe of mind and man’s isolation vis-à-vis society, within the scope of the fantastic as a genre. To do so, I will focus on “Só!” [Alone/Lonely], a short-story published by Machado de Assis in 1885, thus aiming at addressing how the self, the wanderer and the observer appear in this story and how they dialogue with the same figures in some of Poe’s and Baudelaire’s writings.